Prevalence of Staphylococci Among Dental Staff and Their Antibiotic Resistance Pattern - Nadia Kahtan Mahmood; Ghada Younis Abdulrahman; Najwa Ibrahim khaleel (University of Mosul, College of Dentistry, 2023)
Aims: The study aims to estimate the carriage of Staphylococci spp on nares and hands among dental staff and their antibiotic resistance pattern. Materials and Methods: 100 samples were collected from the nose and hands of dental workers (dentists and assistants) in the teaching hospital of the College of Dentistry, University of Mosul from the period 17th Dec. 2020 to 9th Feb.2021. The isolates were diagnosed based on phenotypic traits, microscopy, biochemical test, and the use of the vitek - 2compact device to confirm the species, 66 isolates showed that they were able to ferment mannitol, 32 isolates from the hands, and 34 isolates from the nose while the other isolates showed an inability to ferment mannitol sugar. All Staphylococcus isolates were Gram-positive, catalase 100%, coagulase (18.75%) for hand isolates, and (52.9%) for nosal isolates. Using the vitek 2-compact (40) isolates of fermented mannitol were diagnosed and the results were as follows (20) isolates Staph.aureus 14; (70%) from nose and 6(30%) from hand, 5 isolates of Staph. lugdunensis ;4 (80%) from nose ,1 (20%) from hand .4 isolates Staph. Saprophyticus; 2 (50%) from nose, 2(50%) from hand,2 isolates of Staph. hominis; (100%) from hand,3 isolates of Staph. warneri 2;(66.67%) from nose, 1(33.33%) from hand and one isolate of Staph.sciuri 1,(100) from hand and one isolate of Leuconostoc mesenteroides from hand, four isolates the device couldn't diagnose. The sensitivity of the different isolates to oxacillin was determined with minimum inhibitory concentration (MIC) using vitek2-compact device as oxacillin indicates methicillin in the device. The isolates differed in their resistance to the antibiotic oxacillin where the highest resistance was the percentage to each of Staph.lugdunensis and Staph.sciuri the resistance rate reached 100% followed by Staph.aureus were the resistance rate reached 80% then Staph.warneri 66.67% , Staph.hominis 50% and Staph. Saprophyticus 25% . The sensitivity of different isolates to antibiotics was determined by using Kirby -Bauer method using seven types of antibiotics Staphylococcus isolates showed resistance to both oxacillin and methicillin at percentage 100% except for Staph. Saprophyticus where the resistance was 50%.